Human resource management for the event industry - Van der Wagen, Lynn (Events management series ;, 2015)
"Human Resource Management for the Event Industry still remains the only text to introduce students to the unique application of HR principles in the context of a highly complex event environment. Linking theory, research and application it looks at the purpose and processes of managing such a sizable & varied workforce in a highly pressured environment through the differing and various types of events from sporting to arts to business events. Since the first edition, there have been many important developments in this field and this second edition has been completely revised and updated in the following ways: - extensively updated content to reflect recent issues and trends including: labour markets and industry structure, impacts of IT and social media, risk management, volunteer motivation, talent management, equal opportunities and managing diversity. All explored specifically within the Events Industry - extended volunteer chapter, including new material on ethics, volunteer motivation and satisfaction. - a new chapter on Internal Communications, looks at how an effective internal communication plan can be achieved which is a critical part of HR strategy in the unique event environment. - updated and new international case studies throughout to explore key issues and show real life applications of HRM in the Events Industry. - supported with new lecturer and students online resources including: power point slides, suggested answers to review questions, web & video links to additional resources and a student test bank. Written in a user friendly style, each chapter includes international examples, bulleted lists, guides to further reading and exercises to test knowledge"--